PENINGKATKAN PEMAHAMAN KELOMPOK TANI TERHADAP PENGOBATAN TUBERCULOSIS DAN PENCEGAHANNYA MELALUI FOCUS GROUP DISCUSSION - Abdul Rahem; Wahyu Utami; Andi Hermansyah; Anila Impian Sukorini; Titik Puji Rahayu; Umi Athiyah; Ana Yuda; Arie Sulistyarini; I Nyoman Wijaya; Gusti Noorrizka V; Yuni Priyandani; Aniek Setiya Budiatin; Toetik Aryani; Bambang Subakti Zulkamain (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2024)
Tuberculosis was a cause of global morbidity and mortality. Sumenep Regency has a high number of TBC cases, namely in 2017 were 1,627 people and 1,709 people in 2018. The difficulty in overcoming them is mainly due to the public and drug managers' understanding regarding drug side effects. Therefore, it is necessary to increase their literacy regarding this matter. This research aims to analyze the influence of Focus Group Discussions on farmer group members' understanding of the treatment and prevention of tuberculosis. It also analyzes the understanding of community health center drug managers regarding the side effects of TBC drugs and how to deal with them. A quasi-experimental design, with a pretest – posttest design, was carried out on 49 members of the Bungbungan village farmer group and 39 community health center drug managers in Sumenep. The results showed that the farmer group understanding scores before and after the intervention were as follows: 6.02±1.19 and 6.69±1.46. for drug managers were 14.67±2.41 and 18.36±1.65. Conclusion The Focus Group Discussion had an impact on increasing understanding of the treatment and prevention of tuberculosis for farmer groups, and for community health center drug managers it had an impact on understanding the side effects of TBC drugs and how to deal with them.